(untitled) (Balthazar, 2020)
Nowadays is quite common a very positive vision about what happens in the wild world. We can define it as the idyllic vision of nature. Generally speaking, it can be defined as the idea that in the wild world the positive elements broadly dominate over the negative ones. Specifically, this position is presented within the consideration of what is the situation of the sentient being, and it can be defined in its more concrete meaning as the idea that the sentient beings in the wild world lead lives with more positive than negative elements. The most common version of this vision says that in the wild world happines definitely dominates above pain. Despite the attraction that this position can have on lots of people, there are consistent reasons to think that it reveals itself completely wrong.